EVALUASI ELEKTRODIAGNOSTIK PADA CEDERA SARAF TEPI - Thomas Eko P*, Purna Putra*, Komang Arimbawa * (NEURONA, 2011)
STUDIES ARE HELPFUL IN DEFINING THE EXTENT AND LOCATION OF SUSPECTED PERIPHERAL NERVE INJURY ELECTRODIAGNOSTIC EXAMINATION IS A POWERFUL TOOL FOR DIAGNOSING AND DEVELOPPING TREATMENT PLANS FOR PATIENTS WITH DISEASES OF PERIPHERAL NERVOUS SYSTEM AND MUSCLES THIS TESTING PROVIDES THE MOST VALUABLE DIAGNOSTIC INFORMATION WHEN COMBINED WITH CLINICAL DIAGNOSIS TO OPTIMIZE THE YIELD OF THIS TEST ONE MUST HAVE A BASIC UNDERSTANDING OF HOW IT WORKS WHEN AND HOW TO ORDER IT AND ITS INHERENT LIMITATIONS